PERTUMBUHAN DAN PRODUKSI BEBERAPA GENOTYPE JAGUNG (Zea mays L.) CALON HIBRIDA UMUR GENJAH DAN VARIETAS PEMBANDING BIMA 7 PADA JARAK TANAM YANG BERBEDA - Sulkifli Sulkifli; Nirwana Nirwana; Abdul Haris (Percetakan Umi Toaha Makassar, 2018)
This research was conducted with the aim of: 1) To observe growth and production of maize genotypes hybrid candidate early age, 2) Determine optimal spacing that will result in maximal production of genotype hybrid candidate early maturing and 3) To know interaction between maize genotypes hybrid candidate of early maturing and plant spacing. Research was conducted on dry land located in Bajeng, Gowa, South Sulawesi. Research was conducted from April to July 2017 using Split Plot Design method. As the main plot is the maize genotype consisting of 3 genotypes: ST201328, ST201359, ST201312 and varieties comparison Bima 7 while for sub plot is treatment the various spacing between two levels are: 60 cm x 20 cm and 50 cm x 20 cm. Treatment combination was repeated three times as a block to obtain 24 experimental units. The results of this research show that: 1) Maize genotype ST201328 is maize early maturing hibrid has appearance shortest plant, fastest flowering male age as well flowering female, smallest Anthesis Silking Interval (ASI), fastest harvest age and longer cob. Genotype ST201312 has appearance highest plant, greatest Anthesis Silking Interval, greatest Leaf Area Index and longest cob. 2) Plant spacing 50 cm x 20 cm obtained high Leaf Area Index and highest location cob. Average highest production dry seeds on plant spacing 50 cm x 20 cm for all maize genotypes tested. 3) Interaction that happaned between maize genotype ST201312`on plant spacing 60 cm x 20 cm obtained longest cob is 18,07 cm and differs markedly with varieties comparison Bima 7. Maize genotype ST201312 on plant spacing 50 cm x 20 cm obtained yield dry cheeks is amount 10,58 ton ha–1.